ANALISIS PERANCANGAN SISTEM INFORMASI ARSIP DESA BERBASIS WEB DENGAN METODE WATERFALL DI DESA LINGGASIRNA TASIKMALAYA - Ahmad Zamakhsyari Sidiq; Iwan Kurniawan; Dena Nurkhalija (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
Linggasirna Village is one of the villages located in Sariwangi District, Tasikmalaya Regency. Based on observations, in Linggasirna Village there is no standard system to manage and store village archives, so archive security is not maintained and causes problems searching for archives if at any time needed. Therefore, research was conducted on how to design a web-based village archive information system with the Waterfall method. Based on these methods, research is carried out in stages starting from observation, analysis of system needs. Then, process design, and user interface design to be able to produce a web-based village archive information system design in Linggasirna Tasikmalaya Village. The results of the system design include inputting archive data, uploading archive files into digital data, disposition is carried out computerized, displaying all archives and displaying archive reports according to the required period.